Limnoterrestrial ‘Typhloplanidae’ (Rhabdocoela, Platyhelminthes), with the description of four new species and a new genus - Houben, Albrecht M.; Monnens, Marlies; Proesmans, Willem; Artois, Tom J. (European Journal of Taxonomy, 2022)
Four new species of limnoterrestrial rhabdocoels (‘Typhloplanidae’ Graff, 1905) are described. One of these – Faunulus nielsi Houben, Proesmans & Artois gen. et sp. nov. – could not be unambiguously placed within an existing genus. Faunulus nielsi most closely resembles species of the genus Adenocerca Reisinger, 1924 but can be clearly distinguished by the position of the testes. The three other new species described are Bryoplana belgica Houben, Proesmans & Artois sp. nov., Hoplopera isis Houben, Proesmans & Artois sp. nov., and Protoplanella leiae Houben, Proesmans & Artois sp. nov. All three belong to the subfamily ‘Protoplanellinae’ Reisinger, 1924 and are distinguished based on a detailed description of the reproductive system. Finally, new data are provided for nine other, known typhloplanids: Adenocerca minima Kolasa, 1981; Chorizogynopora italica Kolasa, 1981; Hoplopera opaca Reisinger, 1924; K. subterranea Reisinger, 1933; Krumbachia virginiana (Kepner & Carter, 1931) Ruebush, 1938; Olisthanellinella rotundula Reisinger, 1924; Prorhynchella minuta Ruebush, 1939; Protoplanella simplex Reisinger, 1924; and Ventrociliella romanae Kolasa, 1977. A detailed comparison of our material of V. romanae to what is described for Bockia deses Reisinger, 1924, leads us to consider the latter a nomen dubium.